Mobile Marketing: Pengaruh Aspek Kepercayaan Diri, Kepercayaan Institusi dan Kontrol Diri Pengguna - Diki Gita Purnama (Jurnal Universitas Paramadina, 2016)
AbstractThis study analyzed the consumer behavior using mobile  phone marketing. The growth of mobile marketing usage was  increasing in Indonesia. This gave the opportunity for  marketers to use this technology to capture and to maintain  consumers in the long-term period. This study aimed at  analyzing the consumer behavior to use mobile marketing as  the recipients of information. The study used the  institutional trust, personal trust, perceived control. These  variables were analyzed using survey to a number of  respondents. The respondents were workers and students.  The total number was 83. The sampling uses non-probability  sampling, namely purposive sampling. The  data was analyzed using multiple regression statistics. The  managerial implications were explored to provide vivid  understanding about the usage of mobile marketing in  Indonesia. Only personal trust had positive correlation with  consumer behavior to use mobile marketing.